Risk Factors Linking Esophageal Squamous Cell Carcinoma With Head and Neck Cancer or Gastric Cancer. Issue 4 (April 2019) - Onochi, Kengo; Shiga, Hisashi; Takahashi, So; Watanabe, Noboru; Fukuda, Sho; Ishioka, Mitsuaki; Koizumi, Shigeto; Matsuhasi, Tamotsu; Jin, Mario; Iijima, Katsunori
Abstract : Goals: To investigate retrospectively the risk factors for synchronous and metachronous cancers in the upper gastrointestinal tract in patients with superficial esophageal squamous cell carcinoma (ESCC). Background: In patients who have received endoscopic resection (ER) for ESCC, synchronous and metachronous cancers are frequently detected not only in the esophagus but also in the head and neck area and the stomach. Study: A total of 285 patients who received ER for superficial ESCC were enrolled in this analysis. These patients were periodically followed-up endoscopically. Cumulative occurrence rates of the metachronous second primary cancers were determined by Kaplan-Meier method. Risk factors for synchronous and metachronous cancers in the head and neck area and the stomach were determined by logistic regression analyses. Results: During a mean follow-up period of 76 months, the 5-year cumulative occurrence of metachronous esophageal, head and neck, and stomach cancer was 14.0%, 2.8%, and 4.1%, respectively. Although the presence of multiple lugol-voiding lesions in the esophagus was a significant risk factor for synchronous and metachronous head and neck cancers (odds ratio, 3.8; 95% confidence interval, 1.7-9.0), older age (>65 y) was a significant risk factor for synchronous and metachronous gastric cancer (odds ratio, 3.1; 95% confidence interval, 1.2-9.3). Conclusions: The risk factors for the cooccurrence of head and neck cancer and that of gastric cancer in patients with ESCC differ. This information will likely be useful for managing patients who have been treated with ER for ESCC and who possess carcinogenic potential throughout the upper gastrointestinal tract.